User-Centric Ultra-Dense Networks for 5G - Chen, Shanzhi (SpringerBriefs in Electrical and Computer Engineering,, 2018)
This is the first book to introduce UUDN for 5G, including the concept, challenges, architecture and key technologies. The new network architecture based on "de-cellular" and "user-centric" is proposed with three kinds of decoupling: user plane and control plane decoupling from radio access, control and transmission decoupling from network, local service and network service decoupling. Key characteristics of UUDN are provided, including four aspects: Intelligent network knows user, Moving network follows user, Dynamic network serves user, and Secured network protects user. Four promising technology directions are discussed in detail, including dynamic APs grouping (DAPGing) method, intelligent networking, advanced interference management and user-centric security. The authors also include a UUDN solution, illustrated with numerology and evaluation results as a practical example. Finally, further research directions of UUDN are analyzed. This book gives an overall introduction of UUDN for people who are interested and just begin their study, as well as some suggestions on further research for experts involved in academic, industrial and standardization activities on relative fields.